A Rare Case of Primary Bone Follicular Lymphoma with Multiple Osteolytic Lesions: A Case Report and Review of the Literature - Chiara Togni; Giacinto La Verde; Sabrina Pelliccia; Maria Paola Bianchi; Arianna Di Napoli; Tiziana Lanzolla; Marta Zerunian; Andrea Laghi; Gianluca Maiorana; Ambra Taglietti; Agostino Tafuri (Hemato, 2024)
Introduction: Primary bone lymphoma (PBL) is a rare clinical entity, accounting for less than 5% of all extranodal non-Hodgkin lymphomas and approximately 5% of primary bone tumors. Diffuse large B-cell lymphoma (DLBCL) is the most common histotype, accounting for about 80% of all PBL cases. Conversely, the incidence of indolent primary bone lymphomas (iPBL) represents less than 1% of all reported PBL cases, and data on these rarer lymphomas are scarce. Drawing on diagnostic criteria developed by the World Health Organization (WHO) and the International Extranodal Lymphoma Study Group (IELSG), we report a rare case of primary bone follicular lymphoma, focusing specifically on the clinical presentation and treatment. Discussion: Additionally, we provide a systematic review of the literature data on this very rare lymphoproliferative entity.